THE RELATIONSHIP OF INTERNET ADDICTION WITH SOCIAL INTERACTION IN ADOLESCENTS - ESTER MEINELSA MANURUNG; IDA LISTIANA; MIFTAH AFIFAH ZAHRANI; FENITA PURNAMA SARI INDAH; LUKMAN HANDOYO (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
ABSTRACTThe results of We Are Social and Hootsuite (2020) Indonesia is ranked third with the largest internet access population growth of 17% in the last year or 25.3 million new internet accesses. Indonesia is also ranked eighth in the world with the longest access time where the first rank is the Philippines for 9 hours 45 minutes using internet-facilitated media, while the world average is